The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1007/s00238-006-0082-x
|View full text |Cite
|
Sign up to set email alerts
|

Poor results after interpositional arthroplasty with fascia lata allograft for arthritis of the trapezio-metacarpal joint

Abstract: Arthrodesis or autologous tendon interposition can relieve pain associated with arthritis of the carpometacarpal joint of the first ray (CMC-I), but has its limitations. The aim of this study was to assess whether trapezium resection and fascia lata allograft (Tutoplast) interposition is a good alternative. Thirty-eight such combined CMC-I arthroplasties in 36 patients with a median age of 57 years and a median follow-up of 25 months were analysed for complications; Disabilities of Arm, Shoulder, and Hand ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Previously, outcomes of processed fascia lata allografts have been published. van der Veen et al (8) reported results of 36 patients (38 hands) who underwent a fascia lata interposition after total trapeziectomy without suspension arthroplasty or ligament reconstruction. Mean DASH score was 25 and only 64 % of patients were satisfied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, outcomes of processed fascia lata allografts have been published. van der Veen et al (8) reported results of 36 patients (38 hands) who underwent a fascia lata interposition after total trapeziectomy without suspension arthroplasty or ligament reconstruction. Mean DASH score was 25 and only 64 % of patients were satisfied.…”
Section: Discussionmentioning
confidence: 99%
“…With tendon allografts, operation time can be shortened and donor site morbidity avoided. Results of surgery with processed fascia lata allografts have been reported previously (8,9,10,11). In the present study, fresh frozen human cadaveric tendons from the lower limb were used.…”
Section: Introductionmentioning
confidence: 89%